2015
DOI: 10.1016/j.rmb.2015.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Escarabajos copronecrófagos (Scarabaeidae: Scarabaeinae) de la Reserva Natural Educativa Colonia Benítez, Chaco, Argentina

Abstract: Benítez. Se realizaron 6 muestreos en bosque de quebracho y selva en galería en periodo seco y lluvioso. Los escarabajos se recolectaron mediante trampas cebadas con materia fecal y calamar, y con trampas de luz. Se recolectaron 3,369 ejemplares de 26 especies. Eurysternus aeneus, Canthon quinquemaculatus, Canthon chalybaeus, Deltochilum komareki y Canthidium (Canthidium) sp., representaron el 65% del total de los individuos. Los estimadores no paramétricos de riqueza indican un porcentaje alto de completitud … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…Both species are native to the Chaco region (Medina et al ., ; Damborsky et al ., ; Vaz‐de‐Mello et al ., ). Both species are mainly necrophagous (da Silva et al ., ; Ibarra‐Polesel et al ., ); however, the most abundant feeding resource in livestock areas is cattle dung; we expected coprophagous species to be dominant. While both study areas (North and South) showed similar patterns of species richness and composition between habitat types (lower number of species and similarity in open pastures than in the native forest and the silvopastoral system), local differences were also found; the open pastures in the South area were characterised by lower dominance and higher number of species than those in the North area (24 vs. 16).…”
Section: Discussionmentioning
confidence: 95%
“…Both species are native to the Chaco region (Medina et al ., ; Damborsky et al ., ; Vaz‐de‐Mello et al ., ). Both species are mainly necrophagous (da Silva et al ., ; Ibarra‐Polesel et al ., ); however, the most abundant feeding resource in livestock areas is cattle dung; we expected coprophagous species to be dominant. While both study areas (North and South) showed similar patterns of species richness and composition between habitat types (lower number of species and similarity in open pastures than in the native forest and the silvopastoral system), local differences were also found; the open pastures in the South area were characterised by lower dominance and higher number of species than those in the North area (24 vs. 16).…”
Section: Discussionmentioning
confidence: 95%
“…En contraste, se encontró una mayor abundancia de individuos de Scarabaeinae en bosque natural donde posiblemente se encuentra mayor diversidad y abundancia de mamíferos silvestres que aportan recurso alimenticio para las comunidades de escarabajos copronecrófagos que son sensibles a la abundancia del recurso alimenticio, el tipo de excremento y los cambios en la disponibilidad de estos (Rangel-Acosta et al, 2012). En el bosque natural, los escarabajos copronecrófagos logran colonizar el excremento de mamíferos y posiblemente de aves y de reptiles, pero también aprovechan otros recursos como materia vegetal en descomposición, hongos, frutas y carroña (Bustos y Lopera Toro, 2003;Ibarra-Polesel et al, 2015;Sánchez Hernández et al, 2018), lo que indicaría una mayor cantidad y variedad de recurso que podría significar una mejor dinámica en el bosque, donde los escarabeinos contribuyen con el ciclaje de nutrientes y la dispersión secundaria de las semillas incrementando la regeneración de los bosques (Rangel-Acosta et al, 2012). Para el PUEAR, la presencia de escarabajos supo-ne un servicio de apoyo en la restauración del bosque natural que se encuentra rodeado por otros tipos de vegetación en restauración como el matorral y el páramo antrópico.…”
Section: Discussionunclassified
“…Two exceptions were D. komareki and C. cyanescens , which showed similar attraction to carrion and decomposing fungi (sapro‐necrophagous species). D. komareki has been previously classified as a necrophagous species (Ibarra‐Polesel et al ., 2015) or as a generalist species (Correa et al ., 2016), and C. cyanescens as a coprophagous species (Mayer & Vasconcelos, 2013) or necrophagous species (Gillett et al ., 2010). Differences among studies are probably due to the used baits since none of the previous studies used decomposing fungi as a potential resource.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies were performed either in the field (e.g. Estrada et al, 1993;Ibarra-Polesel et al, 2015;Correa et al, 2016;Wurmitzer et al, 2017) or the laboratory (e.g. Dormont et al, 2004Dormont et al, , 2007Dormont et al, , 2010, whereas few studies have considered both situations (e.g.…”
Section: Discussionmentioning
confidence: 99%